Historical Remarks on the Colonial Typology Towns of La Cabañeta and La Caridad (Hispania Citerior, 2nd-1st century BC): Exploring a Legal-Adinistrative Framework - Espinosa Espinosa, David (Gerión. Revista de Historia Antigua, 2024)
La Cañeta (El Burgo de Ebro, Zaragoza) and La Caridad (Caminreal, Teruel) stand out as exceptional examples of Roman urbanization in Hispania during the Republican period. They are both settlements of colonial typology with origins dating back to the aftermath of the defeat of Numantia by P. Cornelius Scipio Aemilianus around 133/132 BC. According to Appian, this time coincided with the presence of a senatorial commission of decemviri (ἀπὸ τῆς βουλῆς ἄνδρας δέκα), whose aim was to establish the groundwork for pacification and the stable territorial integration of vast regions of Hispania Citerior. This work aims to analyze the available material and institutional evidence from both towns, in order to asses their nature and population, as well as to propose a coherent and plausible historical and legal-administrative framework, which can aid in comprehending and explaining their possible origins, function, and constitutional structures within the context of the military and economic colonization processes promoted by Rome in Italy and Gallia Cisalpina (3rd-2nd centuries BC).